Molecular classification grade 3 endometrial endometrioid carcinoma using a next-generation sequencing–based gene panel - Li, Ling; Chen, Fangfang; Liu, Jingcheng; Zhu, Weifeng; Lin, Liang; Chen, Li; Shi, Yi; Lin, An; Chen, Gang (Frontiers in Oncology, 2022)
Over the past two decades, the incidence of endometrial cancer (EC) is increasing and there is a need for molecular biomarkers to predict prognosis and guide treatment. A recent study from The Cancer Genome Atlas suggested to implement the EC analysis by molecular profile for improving diagnosis, prognosis, and therapeutic treatment. In this study, next generation sequencing was performed on 70 cases of G3 endometrioid endometrial cancers (EEC) using a 11-gene panel (TP53, MLH1, MSH2, MSH6, PMS2, EPCAM, PIK3CA, CTNNB1, KRAS, PTEN and POL) for molecular classification. The molecular classification based on the 11-gene NGS panel identified four molecular subgroups: POLE-ultramutated (n=20, 28.6%), MSI-H (n=27, 38.6%), NSMP (n=13, 18.6%) and TP53mut (n=10, 14.3%). The NGS method showed 98.6% (69 of 70 cases, kappa value 98%) in concordant with the cases assessed by immunohistochemistry (IHC). Among the seven dead cases, four were MSI-H tumors, two were TP53mut/p53abn tumors and one was NSMP tumors with an average OS of 14.7 months. TP53mut subgroup showed poor overall survival rates and POLE group have favorable prognosis. Our work suggested that the 11-gene panel is suitable for molecular classification in G3 EECs and for guiding prognosis and treatment decisions.